Mass media law - Pember, Don R. (McGraw-Hill, 2011)
This current and comprehensive, market-leading textbook addresses the most relevant and important aspects of mass media law in the United States, stretching from the history and adoption of the First Amendment to the most recent judicial opinions, statutory enactments, and regulatory controversies affecting speech across the print, broadcast, cable and Internet media. From the laws of libel and privacy to the regulation of advertising and telecommunications, Mass Media Law examines timely issues that are shaping the United States' legal system and the future of media content